Distribution and biomass of arrow worms (Chaetognatha) in Golfo de Nicoya and Golfo Dulce, Costa Rica - Hossfeld, Britta (1996)
The chaetognath species guild was analyzed from samples collected during the cruise of the German RV Victor Hensen to the Pacific coast of Costa Rica in December 1993 and February 1994. finding the following ten species of the genera Sagitta and Krohnitta: S.enflata, S. hexaplera, S. pacifica, S. neglecta, S. regularis, S. bedoti, S. friderici, S. popovicii, S. pulchra and K. pacifica. Because of their distributional patterns in the study area these species were ascribed to the following ecological groups: neritic, semi-neritic and oceanic. A strong gradient in species richness from offshore to inshore waters (810 one respectively) was found in both gulf systems. In shore chaetognaths were dominated by juveniles and adults of S. friderici in Golfo de Nicoya and by S. popovicii in Golfo Dulce. Biomass spectra were more continuous and of wider range in the Golfo Dulce area showing a dominance of larger chaetognaths. suggesting a more general developed pelagic system in Golfo Dulce, where larger chaetognaths might structure the plankton community by strong grazing pressure from above.